1995
DOI: 10.1002/jemt.1070320402
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting MHC class I expression and class I/class II reciprocity in the CNS: Reconciling divergent findings

Abstract: MHC-restricted T cells are thought to contribute to clinical demyelination in MS and other circumstances. The step-by-step mechanisms involved and ways of controlling them are still being defined. Identification of the MHC+ cells in the CNS in situ has been controversial. This chapter reviews MHC expression in neural tissue, including normal, pathological, experimental, and developing tissue in situ and isolated cells in vitro. A basic pattern is defined, in which MHC expression is limited to nonneural cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0
6

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 86 publications
3
60
0
6
Order By: Relevance
“…CNS resident cells normally express few or no MHC class I molecules (20,21,30,48). In the present study, we demonstrated that MHC class I expression was induced in the CNS after NSV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNS resident cells normally express few or no MHC class I molecules (20,21,30,48). In the present study, we demonstrated that MHC class I expression was induced in the CNS after NSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of neurons to express class I molecules remains controversial. Tissues of the nervous system and primary cultures of neurons do not express detectable levels of MHC class I molecules normally (20,21,30,48). However, MHC class I expression can be induced in neuronal cell lines (5,19) and cultured neurons (32,33,39,50,51) by gamma interferon treatment.…”
mentioning
confidence: 99%
“…We initially expected gene transfer of IFN-␥ to produce an immune reaction because IFN-␥ up-regulates expression of MHC class I molecules in 3LL (data not shown) and drives microglia, a putative APC of the brain, into an immune-active state (11). Our ; groups of these mice, inoculated by 3LL, were treated by either AdIFN (10 l, 2.5 ϫ 10 9 viral particles/ l; scid, n ϭ 9; beige, n ϭ 10) or AdBGAL (10 l, 2.5 ϫ 10 9 viral particles/ l; scid, n ϭ 8; beige, n ϭ 9).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Identifying which cell types express MHC, and therefore which cells can directly interact with and be damaged by T cells, is crucial to understanding the pathogenesis of neurological diseases involving inflammation in animal models and in humans.…”
mentioning
confidence: 99%